ANALISA PRODUKTIVITAS PRODUKSI OLEIC ACID MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) DI PT. PERMATA HIJAU GROUP - Iqbal Habibi; Refiza, Refiza; Rizkha Rida; Sanco Simanullang (Bajang Institute, 2025)
PT. Permata Hijau Group is a company that continues to develop both upstream and downstream, especially at the product sales level. Oleic acid is one of the expensive products sold among oleochemical processing companies. In producing oleic acid, several large costs were found due to lengthy repairs and the plantation not operating. So methods are needed to increase productivity. Analysis using the objective matrix (OMAX) method is a method that is widely used in analyzing the productivity of a company. The method used is the use of OMAX, including determining criteria, determining performance, determining average productivity values, determining the highest and lowest productivity values, determining realistic productivity values, determining scores and value weights, determining productivity indices and making cause-cause diagrams. consequence (fishbone). The results obtained from applying the objective matrix (OMAX) method include the first being the highest productivity index value in October 2023 of 66.66% and the lowest in September of -64.93%. The second result is that the factors that have the most influence on oleic acid productivity. And the third result is that 6 proposed actions are needed to increase oleic acid productivity